Pelvic inflammatory myofibroblastic tumour mimicking scrotal mass: an extremely rare case. Issue 1 (February 2015) - Aykan, Serdar; Akin, Yigit; Basara, Isil; Ates, Mutlu; Tuken, Murat; Uyar, Meral; Nuhoglu, Baris; Semercioz, Atilla
Inflammatory myofibroblastic tumour (IMT) is a rare benign mesenchymal tumour. However, IMT may arise from a wide variety of tissues and is very rare in the elderly. IMT may mimic the mass in which it originates. Although IMT has been defined as uncertain behaviour, it is treated surgically. We present a-65-year old man whose mass was diagnosed as IMT extending from scrotum to pelvis. The mass was independent of any surrounding anatomic structures. According to our best knowledge this is the first case in the literature that pelvic IMT was diagnosed in an elderly man and successfully treated surgically with a long term follow-up period. Aetiology of IMT is still unknown, and more studies are needed for exact continuum of IMT.